A numerical approach for acoustic radiation and scattering of moving bubbles at low frequencies - Li, Yi-Fan; Zhang, Yong-Ou; Qu, Yao; Zhang, Tao (Frontiers in Physics, 2023)
The acoustic radiation and scattering of underwater bubbles play an important role in ocean exploration, target localization, acoustic measurements, etc. The two-phase fluid flow and moving boundary result in the lack of means to predict the sound field, which limits the exploration of relevant characteristics and mechanisms. The present work is intended to introduce a numerical approach for acoustic radiation and scattering of moving bubbles at low frequencies with CFD-BEM coupling method. The two-phase interface is captured with the volume of fluid scheme and the sound field is solved with the boundary element method. After that, some benchmark problems are solved and the results are compared with data from literatures. Finally, the radiation and scattering of moving bubbles at low frequencies are predicted with our approach. The acoustic radiation pressure of bubbles shows a slight increase trend during deformation. As the ka value increases, both the acoustic directionality of radiation and scattering exhibit main and side lobes, and the scattering energy gradually concentrates in the positive direction of the incident wave. For a moving bubble, its displacement and velocity of moving have a significant impact on the directionality of the scattered sound field. Therefore, the problem of bubble localization can be studied based on directionality shift.